Outcomes of Adenotonsillectomy for Obstructive Sleep Apnea in Prader‐Willi Syndrome: Systematic Review and Meta‐analysis. (27th July 2020) - Clements, Anna Christina; Dai, Xi; Walsh, Jonathan M.; Sterni, Laura M.; Prichett, Laura; Boss, Emily F.; Seal, Stella M.; Ryan, Marisa A.
Abstract : Objectives: Prader‐Willi syndrome (PWS) increases the risk of obstructive sleep apnea (OSA) due to obesity, hypotonia, and abnormal ventilatory responses. We evaluated post‐adenotonsillectomy complications, polysomnography changes, and quality of life in children with OSA and PWS. Study Design: Systematic review and meta‐analysis. Methods: We conducted a systematic review and meta‐analysis by searching PubMed, Embase, Cochrane, Web of Science, and Scopus. Two researchers independently reviewed studies about adenotonsillectomy for OSA in patients <21 years with PWS. We extracted study design, patient numbers, age, complications, polysomnography, and quality of life. We pooled postoperative changes in apnea hypopnea index (AHI) for meta‐analysis. We applied Methodological Index for Nonrandomized Studies (MINORS) criteria to assess study quality. Results: The initial search yielded 169 studies. We included 68 patients from eight studies with moderate to high risk of bias. Six studies reported on complications and 12 of 51 patients (24%) had at least one. Velopharyngeal insufficiency was the most commonly reported complication (7/51, 14%). We included seven studies in meta‐analysis. Mean postoperative improvement in AHI was 7.7 (95% CI: 4.9–10.5). Postoperatively 20% (95% CI: 3%–43%) had resolution of OSA with AHI < 1.5 while 67% (95% CI: 50%–82%) had improvement from severe/moderate OSA to mild/resolved (AHI < 5). Two studies evaluated quality of life and demonstrated improvement. Conclusions: Children with PWS undergoing adenotonsillectomy for OSA have a substantial risk of postoperative complications that may require additional interventions, especially velopharyngeal insufficiency. Despite improvements in polysomnography and quality of life, many patients had residual OSA. This information can be used to counsel families when considering OSA treatment options. Laryngoscope, 131:898–906, 2021